(untitled) (Vietnam Journal of Community Medicine, 2021)
Objectives: - Compare the prevalence of depression, anxiety and stress among regularcollege nursing student courses of Bach Mai Medical College in 2021. - Analysis of some factors related to depression, anxiety and stress of regularcollege nursingstudents of Bach Mai Medical College in 2021. Materials and Methods: A cross-sectional descriptive study was conducted on 488 regularcollege nursingstudents, Bach Mai Medical College, interview with DASS-21 questionaire. Results and conclusions: Syntoms of depression, anxiety and stress was recognized in 8.2%; 10.1%; 4.5% of students, respectively. The percentage of students with depression, anxiety and stress has been shown to be highest in the first year students. The mild level ofdepression, anxiety and stresswashighest. Some factors influencing depression, anxiety and stress included: being first-year students; having family economic difficulties; having average or weak academic performance; being unsatisfied with the field of study; drinking alcohol, smokingcigarettes/pipe tobacco; ending a close relationship (friendship); having disagreements with parents.